Pancasila, Keadilan Sosial, dan Persatuan Indonesia - Christian Siregar (Humaniora, 2014)
The rise of separatism that raises with the emergence of separatist groups with their idealistic-communal ideas to create a more democratic and more equitable life recently is quite apprehensive. It is felt in the midst of efforts from various parties—both the government and non-government—to preserve the unity and unification of Indonesia. Should this problem be solved with horizontal conflict and separation option (disintegration) regarding that conflict can’t be and will never be the best solution for problems. This article was made as a response to the related nationality problem with the expectation that this can be one alternative solution for an existing problem-solving effort.